DEGRADASI MINYAK MENTAH DAN SOLAR OLEH KONSORSIUM MIKROBA ASAL PERTAMBANGAN MINYAK CEPU - Joko Prayitno; Esi Liyastuti; Amalia Mahmudah (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2010)
The aim of this research was to obtain oil-degrading microbes from Cepu mining area and to investigate the best combination of microbial consortium to degrade crude and diesel oil. Two yeast isolates were obtained out of ten isolates from Cepu samples. Four best isolates (C7, C6, C4 an C3) were then selected and used for consortium experiments. All consortia either grown in crude or diesel oil showed increased in absorbance values (as the indication of oil degradation) and increased in cell populations at day three. However, pH of the medium decreased from 6.5 at day zero to 2.9-3.5 at day three. After day three, the absorbance values, cell populations and pHs tend to flat or slightly reduced. The best combination of microbial consortium was K3, containing C7, C6 and C4 isolates. This consortium was able to degrade 49-50% of crude or diesel oil for 12 day.